Analisis perbandingan evaluasi knerja portofolio saham sebelum dan di masa pandemi COVID-19 di IDX 30 - Juan Anastasia Putri; Elly Susanti; Ruth Tridianty Sianipar (Owner : Riset dan Jurnal Akuntansi, 2022)
Economic conditions during the Covid-19 pandemic caused portfolio changes when the stock market experienced volatility in March 2020. This impact had an impact on the weak performance of the IDX30 so that many investors experienced panic selling at that time. This is due to the lack of investor knowledge about the formation of stock portfolios, one of which is by using CAPM. This study aims to analyze the formation of a stock portfolio measured using CAPM and analyze the presence / absence of differences in the evaluation of stock portfolio performance as measured using the Sharpe index, Treynor index and Jensen index. These results show the H0 hypothesis is accepted which means that there is no significant difference between testing with the Sharpe, Treynor, and Jensen methods both before and during the Covid 19 pandemic. The test results between treatments both before the Covid-19 pandemic showed that the third difference in the average ranking of the Treynor index, while during the covid-19 pandemic it was the Jensen Index which showed the greatest consistency with the uncertainty between the three measurements.